RELIGIOUS MODERATION : AGAINST INTOLERANCE AND DERADICALIZATION - I Nyoman Alit Putrawan; I Made Gede Nesa Saputra; Kadek Agus Wardana (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
Conflict between religious communities is a sensitive matter that often occurs. This is due to truth claims about various practices that tend to be different from the teachings of the religion adhered to. Indonesia as a country that embraces pluralism does not escape the turmoil of religious conflicts that characterize the life of the nation, so that it has an impact on the loss of tolerance between people and tends to bring up radical principles and coercion of one belief. To produce valid and reliable data, this paper uses a qualitative writing style. In producing logical data, this paper performs several stages of data sorting in the form of: 1). Data reduction, 2). Display data, 3). Verifying data, and 4). Interpret research data. In its presentation, measurable analysis becomes the foundation in processing the data obtained. The perfection of this paper cannot be separated from the library technique carried out by exploring the existing literature in Google Scholar. Truth claims that are too radical tend to foster a sense of intolerance in a nation, this situation will be used by terrorist elements to build a division of the state through religious cloaks. This situation became the center of attention of the Indonesian government so that a program called "the house of religious moderation" was conceptualized to rebuild the dignity of tolerance between religious communities. The legalization of houses of religious moderation begins through educational institutions which in fact are neutral institutions in a country. It is hoped that intellectuals born in educational institutions will be able to provide a concrete understanding of the importance of maintaining tolerance through the values of Pancasila and religious values that are relevant to the situation and stability of the country.